Understanding of source code in language: Contribution of philosophical hermeneutics to the critical code studies. - Bajer, Anna (Digital Scholarship in the Humanities, 2022)
The article discusses the attempt to understand a source code under the conception of philosophical hermeneutics guided by language. Based on a confrontation between H.-G. Gadamer's and Paul Ricoeur's philosophy, our main goal would be searching for the essence of the source code in language. Thus, a closer look is taken into cultural symbols, natural language, and artificial languages. Especially, there would be discussed the problem of abstraction, linguistic community, self-forgetfulness, vitality of formal languages, and display of individuality. This is where the cultural layer of the code can be traced, hence we may find our world-view verbal in nature. In line with the Critical Code Studies approach, in this article, the source code is treated as text. Because of its complexity, the issue should be studied within philosophical inquiry and computer science knowledge. Hence, the perspective developed here goes back to origins and provides a philosophical foundation for Critical Code Studies thinking. The article presents academics with a philosophical challenge: how to understand the source code with an adaptation of a philosophy rejecting artificiality. With philosophical reflection, the source code gains additional meaning and experiences increase in being. Understanding happens in language , which realizes as discourse.